Prevalence and Patterns of Mental Health Disorders in Rural Pakistan: A Cross-Sectional Study from District Mandi Bahauddin - Razzaq, Waheed; Noureen, Amna; Khalid, Fatima; Ramzan, Fatima (Pakistan Journal of Humanities and Social Sciences, 2025)
Across the world, mental health problems are increasing day to day because of increasing day to day challenges and Pakistan is also included in this. Mental disorders especially in the rural areas of Pakistan are also growing day to day and is becoming very common in rural Pakistan due to the lack of facilities and services, socio/economic problems, cultural stigmas and many more. So, the aim of the current study is to determine the prevalence of mental health disorder among the patients in rural district of Pakistan on the basis of the demographic patterns. Across-sectional research method is used to investigate the prevalence of mental health conditions in rural Pakistan. The research was conducted at Idraak Centre of psychiatry, located in District Mandibahaudin, Punjab, Pakistan. The sample for this study included 1,747 individuals who sought treatment at Idraak Centre of psychiatry between March and October2024 and non probability, purposive sampling was used in this study. Data were gathered retrospectively from patients records maintained at Idraak Centre of psychiatry. To ensure data reliability and accuracy the collection process was conducted over a six – month period (March –October 2024). The data was analyzed through SPSS (statistical package of social sciences). Descriptive statistics were used to analyzed the data. Results revealed that Major depressive disorder is a most commonly reported condition in rural areas of Pakistan. Thus, it is very important to work on the infrastructure in which the mental health services should be provided timely and is easily accessible to the people there in rural areas. There should be a proper implementation of community outreach programs, to get people aware from the mental problems and about the proper diagnosis and timely interventions. Furthermore, telehealth mental service should also be provided to the people in rural areas. These all measure with the assurance on the regulations of these rules and policies can be very effective in treating the mental problems of people living in the rural areas.